Adaptations of skeletal muscle mitochondria to exercise training - Lundby, C.; Jacobs, R. A. (Experimental Physiology, 2015)
Here we review recent work relating to exercise-induced alterations in mitochondrial structure and function. Mitochondrial volume density (MitoVD) is composed of two distinct mitochondrial subpopulations 1) intermyofibrillar mitochondria (MitoIMF) and 2) subsarcolemmal mitochondria (MitoSS). With exercise training MitoVD may increase by up to 40% and is for the most part related to an increase in MitoIMF. Exercise-induced adaptations in mitochondrial function depend on the intensity of training and appear to be predominately explained by an increased expression of mitochondrial enzymes that facilitate aerobic metabolism. Although mitochondrial content often increases with training, it seems that mitochondrial adaptations are not needed to facilitate VO2max whereas such adaptations are of greater importance for endurance capacity.